How Strong Is Your Coffee? The Influence of Visual Metaphors and Textual Claims on Consumers’ Flavor Perception and Product Evaluation - Fenko, Anna; de Vries, Roxan; van Rompay, Thomas (Frontiers in Psychology, 2018)
This study investigates the relative impact of textual claims and visual metaphors displayed on the product’s package on consumers’ flavour experience and product evaluation. For consumers, strength is one of the most important sensory attributes of coffee. The 2x3 between-subjects experiment (N=123) compared the effects of visual metaphor of strength (an image of a lion located either on top or on the bottom of the package of coffee beans) and the direct textual claim (“extra strong”) on consumers’ responses to coffee, including product expectation, flavour evaluation, strength perception and purchase intention. The results demonstrate that both the textual claim and the visual metaphor can be efficient in communicating the product attribute of strength. The presence of the image positively influenced consumers’ product expectations before tasting. The textual claim increased the perception of strength of coffee and the purchase intention of the product. The location of the image also played an important role in flavour perception and purchase intention. The image located on the bottom of the package increased the perceived strength of coffee and purchase intention of the product compared to the image on top of the package. This result could be interpreted from the perspective of the grounded cognition theory, which suggests that a picture in the lower part of the package would automatically activate the “strong is heavy” metaphor. As heavy objects are usually associated with a position on the ground, this would explain why perceiving a visually heavy package would lead to the experience of a strong coffee. Further research is needed to better understand the relationships between a metaphorical image and its spatial position in food packaging design.